Clinical and hemodynamic features of acute pulmonary embolism patients diagnosed in cold weather predicts adverse clinical outcome - Sun, Na; Chen, Yiqiang; Liang, Xichao; Fan, Youli; Fang, Ming; Gao, Xuan; Wang, Yongbing; Chen, Yansheng; Wang, Zhuozhong; Yu, Bo; Tian, Jinwei; Wu, Bingxiang (Frontiers in Cardiovascular Medicine, 2022)
Background Acute pulmonary embolism (APE) is associated with peak incidence and mortality rate in winter. The present study sought to characterize the clinical and hemodynamic features of cold weather on APE patients. Methods All enrolled 224 APE patients underwent clinical and hemodynamic evaluation and baseline parameters were collected. Recruited patients were grouped by weather pattern on admission into cold and warm weather group. The correlation and prognostic values among cold weather and other variables were analyzed. Results Compared to warm weather group, patients in cold weather group present with more severe cardiac function, with adverse WHO-functional class (P = 0.032) and higher NT-proBNP concentration [1,853.0 (398.0, 5,237.0) pg/ml vs. 847.5 (56.8, 3,090.5) pg/ml, P = 0.001]. The cold weather group also displayed much critical hemodynamic status and heavier thrombosis load, with higher mPAP (29.1 ± 11.2mmHg vs. 25.6 ± 14.2mmHg, P = 0.045), higher PVR [3.3 (1.7, 6.0) wood units vs. 1.8 (0.9, 3.8) wood units, P < 0.001], higher Miller index (21.4 ± 5.9 vs. 19.1 ± 8.0, P = 0.024), and higher D-dimer levels [2,172.0 (854.5, 3,072.5) mg/L vs. 1,094.5 (210.5, 2,914.5) mg/L, P = 0.008]. Besides, cold weather showed well correlation with the above variables. Survival analysis showed APE patients in cold weather had significantly higher clinical worsening event rate (P = 0.010) and could be an independent predictor of adverse clinical outcome in the multivariate analysis (HR 2.629; 95% CI 1.127, 6.135; P = 0.025). Conclusion APE patients in cold weather were associated with thrombus overload, cardiac dysfunction, hemodynamic collapse and higher clinical worsening event rate. Cold weather proves to be an independent predictor of adverse clinical outcome.